Automation of Time Attendance Machine Data Acquisition through ADMS Features - Hariono, Tholib; Tina Rahmawati Dewi (SAINTEKBU, 2024)
The purpose of this research is to provide convenience for institutions in monitoring employee attendance through the ADMS (Automatic Data Master Server) feature so that information related to measuring employee attendance levels in real time and reliable (cannot be manipulated) can be achieved. This research method uses the Waterfall method where the stages are through Data Analysis, Design, Object research, Implementation and system trials. The results of this study are the results of the implementation there are several conclusions obtained from the design activities of the electronic attendance application, namely the employee data synchronization feature can ensure that employee data in the electronic attendance system is the most up-to-date employee data without the need to re-enter employee data. The use of the ADMS feature in the finger print machine allows sending finger print data in real time, where finger print data that enters the finger print machine at that time can also be sent to the electronic attendance application server. Thus the attendance of each employee can be monitored in real time.